Assessing the Prevalence of Diabetes Distress and Determining Its Psychosocial Predictors Among Saudi Adults With Type 2 Diabetes: A Cross-Sectional Study - Batais, Mohammed A.; Alfraiji, Abdulaziz F.; Alyahya, Abdulrahman Abdullah; Aloofi, Ouf Abdullatif; Almashouq, Mohammad Khalid; Alshehri, Khalid Saeed; Almizel, Abdulrahman Mohammed; Alotaibi, Mohammed Taraheeb; Alosaimi, Fahad D. (Frontiers in Psychology, 2021)
In recent years, the global burden of diabetes distress has increased significantly worldwide, imposing mental health issues on patients and the healthcare system. Hence, this study aimed to estimate the prevalence of diabetes distress and determine its psychosocial predictors among Saudi adults with type 2 diabetes mellitus (T2DM). This cross-sectional, observational study was conducted at Diabetes Clinics, Tertiary Care Academic Medical Center, King Saud University Medical City, Riyadh, Saudi Arabia. The survey questionnaire was distributed to 423 participants. The sample size was 384, where the prevalence of diabetes distress was 48.5%. Based on 5% precision and a confidence interval of 95%, the response rate was 78.25% (334 respondents), among which 61.4% of respondents were females, the remaining 38.6% were males, and the mean age was 56.39 years. The mean scores for the Saudi Arabian Diabetes Distress Scale-17 (SADDS-17) subdomains including emotional burden, physician-related distress, regimen-related distress, and interpersonal distress were 2.63 ± 1.29, 2.31± 1.44, 2.48 ± 1.16, and 2.23± 1.24, respectively. Based on the World Health Organization Quality of Life Assessment Instrument, Short Version (WHOQOL-BREF) transformed scores, the quality of life was recorded as 62.7%. There was a statistically significant positive correlation between the Hospital Anxiety and Depression Scale (HADS) score (r=0.287, p<0.01) and the total SADDS-17 scores. The Patient Health Questionaire (PHQ) 15 scores showed significant positive correlations with the total SADDS-17 scores (r=0.288, p<0.01) and each of the four subdomains. Our present study revealed that diabetes distress prevalence is alarmingly high among patients in Saudi Arabia, Riyadh. Our findings provide evidence that physical symptoms, quality of life, depression, and anxiety are the notable predictors of diabetes distress.